Progress in Coupling Potential Wave Models and Two-Phase Solvers With the SWENSE Methodology - Li, Zhaobin; Bouscasse, Benjamin; Gentaz, Lionel; Ducrozet, Guillaume; Ferrant, Pierre (HAL CCSD, 2018)
International audience